PERAN KOMPLEKSITAS TUGAS SEBAGAI PEMODERASI DALAM MENENTUKAN FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT - Olivia Virlianda; Jaeni (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to analyze the effect of compliance pressure, audit expertise, audit experience, and self-efficacy on audit judgment moderated by task complexity. The technique used in sampling is purposive sampling technique and obtained by 120 people. Data was collected using a survey method with data collection techniques using a questionnaire distributed to the Financial and Development Supervisory Agency (BPKP). The data analysis technique used moderated regression analysis. The results show that compliance does not affect the audit judgment. Meanwhile, audit expertise, audit experience, and self-efficacy affect the audit judgment. The complexity of the task does not strengthen the effect of obedience pressure on audit judgment. In addition, complexity strengthens the effect of audit expertise, audit experience, and self-efficacy on audit judgment.